2021
DOI: 10.3390/ma14061324
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Cured Bisphenolic Epoxy Adhesive Filled with Low Amounts of CaCO3: Effect of the Filler on the Durability to Aqueous Environments

Abstract: The effects of aging exposures to three non-saline aqueous environments on the compressive mechanical properties of a calcium carbonate-filled bisphenolic epoxy adhesive, cold-cured with the addition of two curing agents suitable for the cure at ambient temperature (i.e., Mannich base and triethylenetetramine), were assessed. The amount of the added filler (CaCO3) varied from 1 to 3 g per 100 g of resin; the immersion times in each of the selected medium varied from 1 to 10 months. It was found that the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…During the production of some polymer materials, CaCO 3 , SiO 2 , and other inorganic fillers are often added to glues, rubbers, and other polymeric materials to ensure their mechanical properties and flame retardancy. The results further confirmed that the white spot stains emanated from organic polymer components [32,33]. During the slicing of the silicon wafer, the surface of the silicon wafer will only contact the diamond wire.…”
Section: Resultssupporting
confidence: 64%
“…During the production of some polymer materials, CaCO 3 , SiO 2 , and other inorganic fillers are often added to glues, rubbers, and other polymeric materials to ensure their mechanical properties and flame retardancy. The results further confirmed that the white spot stains emanated from organic polymer components [32,33]. During the slicing of the silicon wafer, the surface of the silicon wafer will only contact the diamond wire.…”
Section: Resultssupporting
confidence: 64%
“…During the production of some polymer materials, to ensure their mechanical properties and ame retardancy, CaCO 3 , SiO 2 , and other inorganic llers are often added to the glues, rubbers, and other polymeric materials. The results further con rmed that the white spot stains were an organic polymer [28,29].…”
Section: Resultsmentioning
confidence: 65%
“…Epoxy resins are used in electronics as well as electrical, automotive, marine, aviation, and construction industries [ 6 , 7 ]. Apart from their main application for joining various materials, they are used as basic components of composites, nanocomposites and laminates [ 7 , 8 , 9 , 10 , 11 ], coatings [ 12 , 13 , 14 , 15 , 16 , 17 ], polymer floors, paints, sealants and impregnates, as well as medical materials characterized by, e.g., antibacterial properties [ 9 , 16 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%